KLASIFIKASI KESALAHAN DAN HAMBATAN PENGGUNAAN BAHASA INDONESIA SEBAGAI BAHASA AKADEMIK PADA MAHASISWA FTK UIN MATARAM - Sultan Sultan; Dwi Yulianingsih (Universitas Islam Negeri Mataram, 2020)
This study aims to (1) classify errors in the use of Indonesianlanguage which include the use of spelling and punctuation, word selection,sentence composition, paragraph preparation in the scientific work of FTKUIN Mataram students; (2) describe the obstacles and solutions for the useof Indonesian in writing scientific papers among students of UIN Mataram.This study uses a descriptive qualitative approach that is supported by verbaldata writing. Data collection in research uses documentation and interviews.The documentation was taken from the fifth semester students’ scientificwork of the Arabic Language Education Department. The results showedthat the errors in the use of Indonesian language of FTK UIN Mataramstudents included 35% letter writing errors, 45% writing punctuation errors,25% word selection errors, and 20% sentence writing mistakes. The obstaclesin the use of Indonesian in the scientific work of students of the Faculty ofEngineering UIN Mataram are language barriers and non-language barriers.Language barriers in the form of not mastering Indonesian languagerules correctly, and non-linguistic barriers include lack of practice andhabituation, control of the results of writing scientific papers for studentsof the Faculty of Engineering UIN Mataram. The solution that can bedone is to get used to the use of Indonesian language based on languagerules, coaching by lecturers through mentoring writing scientific papers. Penelitian ini bertujuan untuk (1) mengklasifikasikan kesalahanpenggunaan bahasa Indonesia yang meliputi pengguanaan ejaan dan tandabaca, pemilihan kata, penyusunan kalimat, penyusunan paragraf dalamkarya ilmiah mahasiswa FTK UIN Mataram; (2) mendeskripsikan hambatandan solusi penggunaan bahasa Indonesia dalam penulisan karya ilmiah dikalangan Mahasiswa FTK UIN Mataram. Penelitian ini menggunakanpendekatan kualitatif deskriptif yang didukung dengan data verbal tulisan.Pengumpulan data dalam penelitian menggunakan dokumentasi danwawancara. Dokumentasi diambil dari karya ilmiah mahasiswa semesterV Jurusan Pendidikan Bahasa Arab. Hasil penelitian menunjukkan bahwakesalahan penggunaan bahasa Indonesia mahasiswa FTK UIN Mataram meliputi kesalahan penulisan huruf 35%, kesalahan penulisan tanda baca45%, kesalahan dalam pemilihan kata 25%, dan kesalahan dalam penyusunankalimat 20%. Adapun hambatan dalam penggunaan bahasa Indonesia dalamkarya ilmiah mahasiswa FTK UIN Mataram adalah hambatan kebahasaandan hambatan non-kebahasaan. Hambatan kebahasaan berupa kurangmenguasai kaidah bahasa Indonesia dengan benar, dan hambatan nonkebahasaanmeliputi kurangnya latihan dan pembiasaan, pengontrolanterhadap hasil menulis karya ilmiah bagi mahasiswa FTK UIN Mataram.Adapun solusi yang dapat dilakukan adalah dengan pembiasaan penggunaanbahasa Indonesia berdasarkan kaidah kebahasaan, pembinaan oleh dosenmelalui pendampingan penulisan karya tulis ilmiah.